Exchange Rate and Covid-19 Pandemic: The Empirical Evidence from Indonesia (Universitas Negeri Semarang, 2023)
This study aims to analyze the influence of various internal and external factors on the movement of the IDR exchange rate. These factors include the Covid-19 pandemic, inflation, interest rates, the money supply and world oil prices. The method used in this study uses Autoregressive Distributed Lag (ARDL) analysis using time series data. The results of this study indicate that the Covid-19 pandemic has a positive effect on the IDR/USD exchange rate in the short and long term. Inflation and interest rates have no effect on the IDR/USD exchange rate in the short or long term. The money supply has an effect in the short term in the current period, one previous period (t-1) and three previous periods (t-3). The influence of the money supply is two-way (positive and negative), while in the long term the money supply has no effect on the IDR exchange rate. World oil prices have a positive effect in the short term in the two previous periods (t-2) and the previous four periods (t-4), as well as in the long term.